Równość versus sprawiedliwość - Bartula, Piotr (Annales. Etyka w Życiu Gospodarczym, 2014)
On the example of a workload dispute (a version of a ‘border dispute’) I present the general problem of two persons – M and P – with equal entitlements to one commodity, which is equally desired by both of them. They are both moderately altruistic; they are not angels untempted by a selfish willingness to get their own way, nor are they devils, who want to destroy others even if it leads to self-destruction. As human beings operating in a world of limited goods, they are so physically and intellectually feeble that neither of them is able to permanently enslave the other and submit him to the second person’s will. Such being the case, each solution to the problem means that the profit of one person is the loss of the second. The question, whether justice is possible at all, suggests itself whether in a situation when people are more or less equal, or with limited altruism and/or selfishness and scarce resources.